A study on the curing kinetics of epoxy molding compounds with various latent catalysts using differential scanning calorimetry. Issue 35 (15th May 2017) - Lee, Da Eun; Kim, Hyun Woo; Kong, Byung‐Seon; Choi, Hyung Ouk
ABSTRACT: We performed kinetic analysis in an epoxy curing system with differential scanning calorimetry (DSC) using a dynamic approach to investigate the reaction behavior of epoxy molding compounds (EMCs) according to three types of catalysts with varying latencies: triphenyl phosphine (TPP), triphenylphosphine‐1, 4‐benzoquinone (TPP‐BQ), and tetraphenylphosphonium tetraphenylborate (TPP‐TPB). In dynamic approach, the well‐known model free kinetic (MFK) method was applied first to find out the variation of activation energy by the extent of conversion. By applying the MFK method, it was found that activation energy as a function of reaction conversion was nearly constant for TPP‐BQ and TPP‐TPB, but significantly reduced for TPP. By the dependence of activation energy, the model fitting method with single step reaction could be applied for TPP‐BQ and TPP‐TPB, and the n th order model was in good agreement with the MFK results. By contrast, in TPP, the reaction curve derived from MFK did not match with plot from n th order model. Isothermal curing experiments were also carried out to determine whether the assumption on kinetic predictions for the three catalysts was correct or not. As a result, TPP‐TPB and TPP‐BQ followed both MFK and n th order model. Nevertheless, TPP was more likely to follow MFK rather than n th order model. In addition, TPP‐TPB showed definitely lower conversion rate and degree of conversion compared with TPP, TPP‐BQ as expected from the catalyst structure and basicity. This study indicates the curing kinetic reaction of EMC depends on the latency of catalysts, and the MFK method can be used to describe the kinetics of curing reaction more accurately. These results help engineers in relevant fields to improve the reliability of EMCs by understanding the curing kinetic reaction of EMC with various latent catalysts. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45252. Abstract :